A golden age : a novel - Anam, Tahmima, 1975- (Shahitya Prakash ; HarperCollins, 2007)
As she plans a party for her son and daughter, Rehana Haque's life will be transformed in a story of one family caught in the middle of the 1971 Bangladesh War of Independence, as they face changes and decisions that will have a profound impact on their lives.